The poetic transformation of binary opposition in the structure of the myth (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the imagery aspect of the unity of opposites andtheir relationship in the language and bellesletters space. Analyzing themethods of reflection of linguistic and literary arts in works of fiction, theauthor argues that such artistic techniques as a description of the personality, the protagonistantagonist, oxymoron, contrasting display, antithesisand stylistic forms are derived from the binary opposition which is inherentin the mythological consciousness. There is also an analysis carried outinto the conflict and nature of the dual characters in contemporary fiction.According to the concepts given in the article it is clear that all the artisticdevices of the opposite structure originated from the tectonics of the binary opposition. The analysis and conclusions in the article concerning binary oppositions, mythological dyads, the unity of opposites are all basedon theoretical works and folklore works of national and world literature.